Just be here [large type] - Davis, Susan Page (Mainely romance, 2024)
"The last thing Nick expects to find when he's out chasing poachers is love. When Libby takes a new job teaching elementary school, she meets a game warden she's drawn to. But Libby and Nick both lack self-confidence and battle memories of difficult relationships in the past. A confrontation with her former fiancé and a traumatic hunting accident tear at Libby. When they agree to put their trust in God, their relationship begins to flourish and they start to make plans for a future together. Yet, a coveted job opportunity could throw a wrench in their plans. If Nick gets the promotion he's dreamed of, will it rip him away from the woman he loves?"--